SWEET FUTURE OF STEVIA: A MAGICAL SWEETENER - Jyoti, Jeevan; Kaur, Maninderjeet; Mishra, Vijay; Mittal, Amit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  The plant Stevia rebaudiana is mainly found in tropical and subtropical regions from western North America to South America. This genus is having near about 240 species of shrubs and herbs in the sunflower family (Asteraceae). It exhibits various properties such as antibacterial, antifungal, anti-inflammatory, antimicrobial, antiviral, antiyeast, cardiotonic, diuretic, hypoglycemic, hypotensive tonic, and vasodilator effect. It is an important source of a number of antioxidants, for example, benzoic acid, caffeic acid, chlorogenic acid, ferulic acid, rozmaric acid, protocatechuic acid, salicylic acid, and their derivatives and flavonoids including campherol derivatives, catechin, and its derivatives, epicatechin, luteolin, and its derivatives, rutin, and its derivatives. Day by day, there is remarkable increase in demand of high potency sweeteners. The increasing number of diabetic patients and health conscious individuals would push forward the need for alternatives to sugar. The extract from leaves of Stevia is 200 times sweeter than sugar (glucose, fructose, sucrose, maltose, and lactose). Stevia is a potential alternative source for replacing artificial sweeteners such as saccharin, aspartame, and asulfam.